2023
DOI: 10.3390/molecules28124645
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Development of Bivalent Aptamers Blocking SARS-CoV-2 Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused devastation to human society through its high virulence, infectivity, and genomic mutations, which reduced the efficacy of vaccines. Here, we report the development of aptamers that effectively interfere with SARS-CoV-2 infection by targeting its spike protein, which plays a pivotal role in host cell entry of the virus through interaction with the viral receptor angiotensin-converting enzyme 2 (ACE2). To develop highly effective aptamers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The aptamer was developed by VIRO-SELEX [ 25 , 26 ]. Several cycles of VIRO-SELEX were performed, and a pool of 11 cycles was chosen to analyze the sequence [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The aptamer was developed by VIRO-SELEX [ 25 , 26 ]. Several cycles of VIRO-SELEX were performed, and a pool of 11 cycles was chosen to analyze the sequence [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Monomeric proteins may be simultaneously targeted by two aptamers, thus forming ternary complexes (1ˆ:2 or 1:2 in Table 1). In particular, eight structures of ternary complexes involving either thrombin (entries #62, 63, 104, and 129-131 PDB IDs 5EW1, 5EW2, 7NTU, 7ZKM, 7ZKN, and 7ZKO) [82,107,114] or the spike protein S1 from SARS-CoV-2 (entries #143 and 144, PDB IDs 8J1Q and 8J26) [119] have been reported until now.…”
Section: Ternary Complexesmentioning
confidence: 99%
“…Interestingly, the analysis of the interacting surface of TBA and thrombin at exosite II, which is non-canonical for this aptamer, indicated that it is similar to the interface area of TBA at exosite I and different from the surfaces commonly detected in the complexes with HD22_27mer and Toggle-25t aptamers targeting exosite II with high affinity (Figure S3). Finally, in the last year, the cryo-EM structures of two 1:2 ternary complexes (entries #143 and 144, PDB IDs 8J1Q and 8J26) [119] in which the receptor-binding domain (RBD) of SARS-CoV-2 spike protein S1 is simultaneously bound to two different aptamers, AM032-0 and AM047-0, or their derivatives, at two distinct binding sites, were reported (Figure 6c). These studies showed that the binding of angiotensin-converting enzyme 2 (ACE2), the viral receptor protein of the host cell, to the spike protein S1 is hindered by the AM032 aptamer family.…”
Section: Ternary Complexesmentioning
confidence: 99%
See 1 more Smart Citation